Isolation and In vivo Transfer of Antigen Presenting Cells - Arora, Pooja (Bio Protoc, 2014)
Transfer of antigen presenting cells in vivo is a method used by immunologists to examine the potency of antigen presentation by a selected population of cells. This method is most commonly used to analyze presentation of protein antigens to MHC class I or II restricted T cells, but it can also be used for studies of nonconventional antigens such as CD1-presented lipids. In a recent study focusing on CD1d-restricted glycolipid antigen presentation to Natural Killer T cells, we compared antigen presenting properties of splenic B cells, CD8α(Pos) dendritc cells (DCs) and CD8α(Neg) DCs (Arora et al., 2014). This protocol describes the detailed method used for isolation of these cell populations, and their transfer into recipient mice to analyze their antigen presenting properties.